Sustainability management control system and sustainability performances in Indonesia - Kurnianto, Sigit; Tjahjadi, Bambang (International Journal of Management and Sustainability, 2025)
This study aims to determine the effect of the Sustainability Management Control System (SMCS) on improving Sustainable Performance (SP) or corporate sustainability performance. The study utilizes the data from 412 non-financial companies listed on the Indonesia Stock Exchange, covering the period from 2017-2021. Hypothesis testing was carried out with a least squares regression model strengthened by robustness tests. To support the results, a number of other studies were carried out, including panel data, sensitivity testing, and the coarsened exact matching approach. The results showed a positive correlation between SMCS and improving sustainability performance. This means that the better the implementation of SMCS in a company, the more its sustainability performance will improve. This indicates the important role of SMCS in supporting the improvement of corporate sustainability performance. The practical implication of this research is to provide insight for executives, policymakers, and stakeholders to encourage the implementation of SMCS to achieve the success of sustainable development. In terms of theoretical contribution, this research elucidates the relationship between SMCS and sustainability performance, highlighting that SMCS is a development of the Management Control Systems (MCS) concept, incorporating new metrics. Overall, this research is useful for understanding the effectiveness of SMCS in improving corporate sustainability performance.